China's second continent : how a million migrants are building a new empire in Africa - French, Howard W., 1957- (New York : Vintage Books, 2015)
Americký novinář popisuje rostoucí roli Číny a čínských migrantů na africkém kontinentu.
Keywords: imigranti; emigrace a imigrace; immigrants; emigration and immigration; Čína; Afrika subsaharská; China; Africa, Sub-Saharan; monografie; monographs